2013
DOI: 10.1039/c2dt32441e
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on Grubbs’ pre-catalyst initiation rates

Abstract: Initiation rates for Grubbs and Grubbs-Hoveyda second generation pre-catalysts have been measured accurately in a range of solvents. Solvatochromic fitting reveals different dependencies on key solvent parameters for the two pre-catalysts, consistent with different mechanisms by which the Grubbs and Grubbs-Hoveyda pre-catalysts initiate.The alkene metathesis reaction is now a standard transformation in academic laboratories, and has been applied to the synthesis of a wide range of natural 1,2 and unnatural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
3
30
1
Order By: Relevance
“…These data showed that toluene and THF produced polymers with lower PDI (PDI < 1.2) and resulted in higher conversions (>82% based on GPC) than chloroform. This was primarily attributed to differences in the initiation rates as has been reported previously by Ashworth et al and Sanford et al, where initiation rates of Grubbs' catalysts are higher in THF and toluene than in chloroform. The 1 H‐NMR results from these experiments were consistent with the previously published trends and indicated that G2 reached equilibrium between the inactive and active catalyst species 2–4 times faster in d 8 ‐THF than in CDCl 3 (see Supporting Information Figs.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…These data showed that toluene and THF produced polymers with lower PDI (PDI < 1.2) and resulted in higher conversions (>82% based on GPC) than chloroform. This was primarily attributed to differences in the initiation rates as has been reported previously by Ashworth et al and Sanford et al, where initiation rates of Grubbs' catalysts are higher in THF and toluene than in chloroform. The 1 H‐NMR results from these experiments were consistent with the previously published trends and indicated that G2 reached equilibrium between the inactive and active catalyst species 2–4 times faster in d 8 ‐THF than in CDCl 3 (see Supporting Information Figs.…”
Section: Resultssupporting
confidence: 53%
“…mPEGCB exhibited the smallest k 1 value compared to the other two monomers. This was attributed to the presence of the oxygen atoms from the PEG side chains, which can affect the overall polarizability of the solvent and thus change the ligand dissociation rate constants . The mPEGCB monomer showed the largest k 2 / k −1 value (4.03) indicating that its reaction intermediate will favor coordination to the cycloolefins to open the cyclobutene ring, rather than recoordination with PCy 3 to deactivate the catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, almost quantitative conversion is achieved in the first 10 minutes of the reaction (Figure ). This change of “reactivity” can be explained not only by temperature increase giving more energy to transition states, but also by an aromatic solvent effect, which probably can destabilize substrate–catalyst complex …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the decrease in concentration of catalyst 10 was found to be first order ( Figure 10) and allowed the rate of initiation of the polymerisation of monomer 8a (k i8a ) to be determined as 1.76 x 10 -4 s -1 at 298 K. This value compares well with the value of 1.4 x 10 -4 s -1 previously determined for initiation of other metathesis reactions in dichloromethane at 298 K using catalyst 10. 37,38 This is to be expected as the rate determining step of metathesis initiation by complex 10 is known to be dissociation of its tricyclohexylphosphine ligand, a process which is independent of the alkene to be metathesised. 39 Figure 10: First order kinetic plots for the determination of ki8a (red), kp8a (blue) and kp8b (green).…”
Section: Resultsmentioning
confidence: 99%